2019
DOI: 10.3389/fnins.2019.01321
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Neuroimaging Data Through Recurrent Deep Learning Models

Abstract: The application of deep learning (DL) models to neuroimaging data poses several challenges, due to the high dimensionality, low sample size and complex temporo-spatial dependency structure of these datasets. Even further, DL models act as as black-box models, impeding insight into the association of cognitive state and brain activity. To approach these challenges, we introduce the DeepLight framework, which utilizes long short-term memory (LSTM) based DL models to analyze whole-brain functional Magnetic Resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 65 publications
1
75
0
Order By: Relevance
“…Only recently, it became possible to apply more powerful models such as deep neural networks without sacrificing interpretability. These explainable non-linear models have already attracted attention in domains such as neuroscience [87,89,20], health [33,14,40], autonomous driving [31], drug design [70] and physics [78,72] and it can be expected that they will play a pivotal role in future scientific research.…”
Section: Explanations Are a Prerequisite For New Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, it became possible to apply more powerful models such as deep neural networks without sacrificing interpretability. These explainable non-linear models have already attracted attention in domains such as neuroscience [87,89,20], health [33,14,40], autonomous driving [31], drug design [70] and physics [78,72] and it can be expected that they will play a pivotal role in future scientific research.…”
Section: Explanations Are a Prerequisite For New Insightsmentioning
confidence: 99%
“…They not only outperform humans in complex visual tasks [16,53] or strategic games [56,83,61], but also became an indispensable part of our every day lives, e.g., as intelligent cell phone cameras which can recognize and track faces [71], as online services which can analyze and translate written texts [11] or as consumer devices which can understand speech and generate human-like answers [90]. Moreover, machine learning and artificial intelligence have become indispensable tools in the sciences for tasks such as prediction, simulation or exploration [78,15,89,92]. These immense successes of AI systems mainly became possible through improvements in deep learning methodology [48,47], the availability of large databases [17,34] and computational gains obtained with powerful GPU cards [52].…”
Section: Introductionmentioning
confidence: 99%
“…1. Illustration of the DeepLight framework [13]. DeepLight first separates a wholebrain fMRI volume into a sequence of axial slices.…”
Section: And [1])mentioning
confidence: 99%
“…Training All DeepLight variants that were used in this study were trained as follows (if not reported otherwise): We iteratively trained DeepLight through backpropagation, by the use of the ADAM optimization algorithm, as implemented in tensorflow 1.13. During parameter estimation, we applied dropout regularization to all network layers as follows: We set the dropout probability to 50 % for the LSTM unit and softmax output layer, For the convolution layers, however, we set the dropout probability to 0% for the first four convolution layers, 20% for the next four convolution layers, and 40% for the last four convolution layers (in line with [13]). We further used a learning rate of 1e −4 and a batch size of 24 fMRI volumes.…”
Section: Deeplightmentioning
confidence: 99%
See 1 more Smart Citation